Pengaruh Pembiasaan Amal Yaumiyah Terhadap Disiplin Belajar Fikih Siswa di SMP Islam Terpadu Ar-Risalah Sukoharjo Tahun Ajaran 2025/2026 - Maisaroh, Samrotul Janah; Nashir, Muhammad Ja'far (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to examine the influence of daily religious habituation (amal yaumiyah) on students' discipline in learning fiqh at SMP Islam Terpadu Ar-Risalah Sukoharjo in the academic year 2025/2026. Daily religious habituation refers to routine religious activities practiced by students to cultivate religious values and discipline in everyday life. This research employed a quantitative approach with a correlational research design involving 51 students as participants. Data were collected through questionnaires and documentation, and the instruments were tested for validity and reliability. Data analysis was conducted using simple linear regression with the assistance of SPSS version 25. The results show that daily religious habituation has a positive and significant influence on students' discipline in learning fiqh, as indicated by the correlation coefficient (R) of 0.647 and the coefficient of determination (R²) of 0.419. This means that daily religious habituation contributes 41.9% to students' learning discipline in fiqh, while the remaining percentage is influenced by other factors outside the research variables.